2008
DOI: 10.1037/0012-1649.44.1.15
|View full text |Cite
|
Sign up to set email alerts
|

"Mostly straight" young women: Variations in sexual behavior and identity development.

Abstract: Researchers have begun to explore and identify various gradations in sexual orientation identity, paying attention to alternative sexual identity categories and attempting to clarify potential subtypes of same-sex sexuality, particularly among women. This study utilizes both quantitative and qualitative data to explore the behavioral experiences and identity development processes among women of a particular sexual identity subtype, "mostly straight." Participants were 349 female college students whose primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
128
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 46 publications
15
128
2
4
Order By: Relevance
“…Indeed, variations in sexual orientation have been a topic of increasing interest in the study of sexuality (Ott et al, 2011;Thompson and Morgan, 2008), including with regard to alcohol use (Marshal et al, 2008;McCabe et al, 2011;Midanik et al, 2007). The extant literature has relied on entrenched variable-centered approaches or long-held assumptions that conceptualize sexual orientation as largely immutable or one-dimensional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, variations in sexual orientation have been a topic of increasing interest in the study of sexuality (Ott et al, 2011;Thompson and Morgan, 2008), including with regard to alcohol use (Marshal et al, 2008;McCabe et al, 2011;Midanik et al, 2007). The extant literature has relied on entrenched variable-centered approaches or long-held assumptions that conceptualize sexual orientation as largely immutable or one-dimensional.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual identity development process is inherently stressful for some persons (Thompson and Morgan, 2008). Indeed, sexual questioning is often accompanied by increased feelings of alienation and isolation (Glover et al, 2009;Savin-Williams and Diamond, 1999;Thompson and Morgan, 2008;Yarhouse and Tan, 2004). We speculate that some sexual minority individuals may use alcohol to cope with negative affectivity or to fi t in with a desired social group as they grapple with issues inherent in sexual identity development processes.…”
Section: Discussionmentioning
confidence: 99%
“…As the quotes from participants in this study further illustrate, and as psychology textbooks sometimes obscure (Barker, 2007;Hogben & Waterman, 1997), some male and female students identify as bisexual. Reducing reliance on such textbooks would both counter the problem of androcentrism in the psychology of sexual minorities (Lee & Crawford, 2006), and recognize the experiences of students who identify as bisexual, queer (Minton, 1997), and 'mostly straight' (Thompson & Morgan Thompson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this group tends to be neglected in many studies, a few researchers have recently addressed the uniqueness of this particular group being distinct from exclusively heterosexual and lesbian/gay/bisexual (LGB) individuals (Austin, Conron, Patel, & Freedner, 2007;Austin, Roberts, Corliss, & Molnar, 2008;Saewyc et al, 2004;Thompson & Morgan, 2008;Savin-Williams & Vrangalova, 2013). In earlier research, this group has been estimated 6% to 10%, as compared to LGB peers estimated 1% to 4% (e.g., Austin, Ziyadeh, Fisher, Kahn, Colditz, & Frazier, 2004a;Saewyc, Richens, Skay, Reis, Poon, & Murphy, 2006;Saewyc et al, 2011), and found to be at higher risk than exclusively heterosexual peers for smoking (Austin et al, 2004a), eating disorder (Austin, Ziyadeh, Kahn, Camargo, Colditz, & Field, 2004b), and sexual risk behavior (Saewyc et al, 2006).…”
mentioning
confidence: 99%